The Migration and Transformation of Heavy Metals in Sewage Sludge during Hydrothermal Carbonization Combined with Combustion - Liu, Meng (Biomed Res Int, 2018)
The migration and transformation behaviors of heavy metals (HMs), including Cr, Mn, Ni, Cu, Zn, As, Cd, and Pb, during the hydrothermal carbonization (HTC) of sewage sludge (SS) were investigated. The immobilization of HMs during the combustion of solid residual (SR) produced from HTC of SS was also analyzed. With increasing HTC temperature and residence time, the majority of HMs (except As) accumulated in the SR. The residual rate of As in the SR decreased from 73.95% to 56.74% when the residence time was increased from 1h to 3h and reduced significantly from 73.95% to 37.48% when the temperature increased from 220°C to 280°C, implying that numerous arsenic compounds dissolved into liquid phase products. Although the HTC process has a positive influence on the transformation of HMs from weakly bound fractions to the more stable fractions, the exchangeable and reducible fractions of Mn, Zn, As, and Cd in the SR were still high. In addition, the leached amounts of Zn and As were high (14.61 and 6.16 mg/kg, respectively) and showed a high leaching risk to the environment. An increase in HTC temperature and residence time led to an increase of the residual rate of HMs in the combustion residual of SR, implying that the HTC process promotes the stabilization of HMs in the combustion process.